The Impact of Online Application Competition, Discount Prices and Cinemax Service Innovation on Online Cinema Ticket Purchase Decisions in Medan City - Safira Nurul Sakinah Kacaribu; Hendra Jonathan Sibarani (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study was conducted to explain the impact of online application competition, discounted prices, and Cinemax service innovation on online cinema ticket purchasing decisions in Medan. The quantitative descriptive method is used in the research. The online cinema ticket ordering application (TIX ID) in the East Medan area is 112,482 people, and the sampling technique using the slovin formula is obtained by 100 respondents. The results of this study are the application competition variable (X1) obtained a value of thtung> t-table (3.935> 1.290), the discounted price variable (X2 ) obtained a value of t-count> t-table (1.715> 1.290), the service innovation variable (X3) obtained a value of thtung> t-table ( 5.795 > 1.290 ) has a significant positive effect with a value of < 0.1 on online cinema ticket purchasing decisions in the city of Medan.